Desenvolvimento de um sistema misto de pasta à base de geopolímero e cimento portland para correção de perda de circulação - Barros, Marcus Vinicius Cavalcanti (2013)
The materials engineering includes processes and products involving several areas of engineering, allowing them to prepare materials that fulfill the needs of various new products. In this case, this work aims to study a system composed of cement paste and geopolymers, which can contribute to solving an engineering problem that directly involves the exploitation of oil wells subject to loss of circulation. To correct it, has been already proposed the use of granular materials, fibers, reducing the drilling fluid or cement paste density and even surface and downhole mixed systems. In this work, we proposed the development of a slurry mixed system, the first was a cement-based slurry and the second a geopolymer-based slurry. The cement-based slurry was formulated with low density and extenders, 12.0 ppg (1.438 g/cm ³), showing great thixotropic characteristics. It was added nano silica at concentrations of 0.5, 1.0 and 1.5 gps (66.88, 133.76 and 200.64 L/m3) and CaCl2 at concentrations of 0.5, 1, 0 and 1.5%. The second system is a geopolymer-based paste formulated from molar ratios of 3.5 (nSiO2/nAl2O3), 0.27 (nK2O/nSiO2), 1.07 (nK2O/nAl2O3) and 13.99 (nH2O/nK2O). Finally, we performed a mixture of these two systems, for their application for correction of circulation lost. To characterize the raw materials, XRD, XRF, FTIR analysis and titration were performed. The both systems were characterized in tests based on API RP10B. Compressive strength tests were conducted after curing for 24 hours, 7 and 28 days at 58 °C on the cement-based system and the geopolymer-based system. From the mixtures have been performed mixability tests and micro structural characterizations (XRD, SEM and TG). The results showed that the nano silica, when combined with CaCl2 modified the rheological properties of the cement slurry and from the concentration of 1.5 gpc (200.64 L / m³) it was possible to obtain stable systems. The system mixture caused a change in the microstructure of the material by favoring the rate of geopolymer formation to hinder the C3S phase hydration, thus, the production of CSH phases and Portlandite were harmed. Through the mixability tests it can be concluded that the system, due to reduced setting time of the mixture, can be applied to plug lost circulation zones when mixed downhole